Adults miscoded and misdiagnosed as having pneumonia: results from the British Thoracic Society pneumonia audit. Issue 4 (20th January 2017) - Daniel, Priya; Bewick, Thomas; Welham, Sally; Mckeever, Tricia M; Lim, Wei Shen
Abstract : A key objective of the British Thoracic Society national community-acquired pneumonia (CAP) audit was to determine the clinical characteristics and outcomes of hospitalised adults given a primary discharge code of pneumonia but who did not fulfil accepted diagnostic criteria for pneumonia. Adults miscoded as having pneumonia (n=1251) were older compared with adults with CAP (n=6660) (median 80 vs 78 years, p<0.001) and had more comorbid disease, significantly fewer respiratory symptoms (fever, cough, dyspnoea, pleuritic pain), more constitutional symptoms (general deterioration, falls) and significantly lower 30-day inpatient mortality (14.3% vs 17.0%, adjusted OR 0.75, p=0.003).